Developing Computationally Efficient Property Calculations for High-Pressure, Multi-Component Droplet Vaporization - Hayes, Michael Patrick (Proceedings of the Wisconsin Space Conference, 2022)
The combustion of liquid fuels such as gasoline, diesel, and jet fuels often occurs at elevated pressures. The complex composition of these hydrocarbon fuels makes modeling them a time-consuming process using traditional discrete component models (DCMs); continuous thermodynamic models (CTMs) are more computationally efficient. This paper utilizes high-pressure property calculations to improve upon the accuracy of an existing CTM in depicting the vaporization of liquid fuel droplets at high pressures. Increased model fidelity in replicating DCM results is accomplished by depicting these properties as functions of temperature, pressure, and a chosen distribution variable. This addition leads to high simulation accuracy at elevated pressures while maintaining the computational efficiency of CTMs.